The Relationship Between Self-Efficacy, Job Satisfaction, and Medical Personnel Performance: A Psychological Review - Yuliaty, Farida; Dewi, Ni Putu Ayu Yusita (Amkop Management Accounting Review (AMAR), 2025)
This research aims to analyze the complex relationship between self-efficacy, job satisfaction, and medical personnel performance through a comprehensive psychological review. Using qualitative methods with a library research approach, this study explores relevant literature from 2019-2025 to build a deep theoretical understanding of the interrelationship between these three psychological variables. Thematic analysis reveals that self-efficacy functions as the main predictor of medical personnel performance through psychological mechanisms involving professional confidence, intrinsic motivation, and adaptive capacity. Job satisfaction serves as a partial mediator that creates a positive spiral in the relationship between self-efficacy and performance, where medical personnel with high efficacy experience greater job satisfaction and produce optimal performance. The findings show a complex reciprocal relationship where good performance increases self-efficacy through successful experiences and positive feedback. The resulting conceptual model provides strategic implications for developing healthcare HR management programs that focus on improving self-efficacy and job satisfaction as sustainable investments for optimizing medical personnel performance and healthcare service quality.